Peramalan Kebutuhan Mangan Domestik Menggunakan Model Time Series Dan Analisis Dampak Ekonomi Sektor Pertambangan Mangan Terhadap Perekonomian Nasional (Jurnal Geomine, 2020)
Management of national manganese ore mines have not resulted in maximal, so Indonesia still imports manganese ore to meet the supply needs of the manganese smelters as suppliers to the steel industries in the country. To determine the number of national steel consumption until 2019, forecasting models are required to project the consumption of steel in those years. The results of these projections will be used as a reference for calculating the needs of manganese ore as one of the compounds that are used for steelmaking. Forecasting the national steel consumption is using time series models, the economic impact of the management of manganese mining sector is calculated using National Input-Output Table 2010. The total requirements of manganese ore based on national steel consumption in 2014-2019 are 4,696,898.41 tons, The economic impact of the manganese mining sector output is Rp 13,173 trillion.